Collapsible characteristics of loess tunnel site and their effects on tunnel structure. (January 2019) - Li, Jun; Shao, Shengjun; Shao, Shuai
Abstract: During the infrastructure construction process in the loess region of Northwest China, some tunnels are inevitably located in collapsible loess strata, and the potential collapsible deformation of the surrounding loess may threaten the safety and stability of the tunnel structure. To investigate the functional mechanism of loess strata hydrocollapse for a tunnel structure, a large field water immersion test was conducted in this study on the ground surface above an existing loess tunnel. The subsidence of the strata and the mechanical response of the tunnel structure during long-term water immersion were measured and analysed to reveal the collapsible deformation characteristics of the loess tunnel site and their effects on the tunnel structure. The results show that the surface water could infiltrate into the base of the tunnel and that a large deformation occurred in the surrounding loess near the tunnel vault once the loess was wetted. As the water infiltrated to the burial depth of the tunnel, the base pressure increased significantly, the tunnel structure subsided and the inverted arch cracked. Therefore, for a loess tunnel with a relatively shallow burial depth, long-term water immersion above the tunnel should be avoided, and the possibilities of decreasing bearing capacity and tunnel foundation subsidence at the arch feet caused by wetting must be considered during design and construction.